أسلوب الترغيب والترهيب مع أهل الكتاب في سورتي البقرة وآل عمران = Method of the excitement and intimidation with people of the book in surah Al-Baqarah and Al Imran - Shkokani, Najwa Naief; Elatrash, Radwan Jamal Yousef; Banaderi, Farzaneh Balali (Iraqi Academic Scientific Journals, 2018)
The purpose of this research is to highlight the method of excitement and intimidation with the people of the book in the Sourat al-Baqarah and Ali ‘Imran. and to show the personality of the people of the book. However, the call of the people of the Book must be made by influential methods. This style is among their preaching methods in which there is preaching with happy news and warning. and it shows the emotional approach in which to bring benefit and pay harmful. Using the method of inductive and analytical reasoning by collecting information from ancient and modern sources related to the subject, and the Quranic verses in which the method of excitement and intimidation with the people the book in the two sections of the cow and Ali ‘Imran, analyzed and used. Thus, it concludes that the Soras are rich in excitement and intimidation with the people of the book, and that the contemporary Muslim can benefit from the method at any time and place, taking into account, of these invitees and their circumstances. ********************************************************** يهدف هذا البحث إلى إبراز أسلوب الترغيب والترهيب مع أهل الكتاب في سورتي البقرة وآل عمران، وإظهار شخصية أهل الكتاب فيها، ولانّ دعوة أهل الكتاب يجب أن تكون بأساليب مؤثرة لما يحملون من اعتقادات منحرفة فاسدة تمنعهم من قبول الحق والدخول في الإسلام، وهذا الأسلوب هو من وسائل دعوتهم فيه البشارة والإنذار، ويظهر فيه المنهج العاطفي وفيه جلب منفعة ودفع مضرة، وقد استخدم في البحث المنهج الاستقرائي والتحليلي وذلك من خلال جمع المعلومات من المصادر القديمة والحديثة المتعلقة بالموضوع، والآيات القرآنية التي وردت فيها أسلوب الترغيب والترهيب مع أهل الكتاب من خلال سورتي البقرة وآل عمران، وتحليلها والاستفادة منها. وخلصت إلى نتيجة أن السورتان تزخران بأسلوب الترغيب والترهيب معهم، وأن المسلم المعاصر يستطيع أن يستفيد من ذلك الأسلوب في أي زمانٍ ومكانٍ مراعياً أحوال هؤلاء المدعوين وظروفهم.